Abdul Haris Nasution's Contributions to Indonesian Military and Politics: 1955-1959 - Wahyudi Malinau; Rhoma Dwi Aria Yuliantri (Diakronika, 2023)
This article is a historical study that discusses Abdul Haris Nasution from a political perspective. This research explores Abdul Haris Nasution's career journey and his contributions to the Indonesian military and politics from 1955 to 1959. This study uses historical methods with steps, namely heuristic, verification, interpretation, and historiography. The historical sources used are primary sources, including the Chiefs Staff of mandate in the Republic of Indonesia, Instructions of the Central Warlord, The Mimbar Indonesia, and Nasution's writing books. Secondary sources from the results of previous research, which became the basis of Nasution's thought on the military and politics, such as Abdul Haris Nasution's role in the "Bandung Lautan Api" incident in 1945–1946 and Abdul Haris Nasution's role in the liberation of West Irian, 1957–1962. The results of this research show that Nasution's career in the military field was very bright, starting with joining the Reserve Officers Corps (CORO). On October 17, 1952, Nasution resigned from the Chief of Staff of the Army (KSAD) position and returned to active service in the military in 1955. Nasution contributed to the military field in 1955–1959 to formulate ideal civil-military relations in Indonesia and the "middle way" army concept. Nasution's contribution to the political field in 1955–1959 re-implemented the 1945 Constitution. Nasution encouraged President Soekarno to issue a presidential decree as the beginning of guided democracy.